Physical Activity as a Coping Strategy for Mental Health Due to the COVID-19 Virus: A Potential Disconnect Among Canadian Adults? - Faulkner, Guy; Rhodes, Ryan E.; Vanderloo, Leigh M.; Chulak-Bozer, Tala; O'Reilly, Norm; Ferguson, Leah; Spence, John C. (Frontiers in Communication, 2020)
COVID-19 was declared a global pandemic by the World Health Organization on March 11, 2020. The COVID-19 pandemic and resulting social disruption has left many to struggle with changes to routines and feelings of uncertainty as the impact of the virus continues to unfold. Evidence suggests an increase in symptoms of anxiety, depression, and stress as a result. Given the well-documented association between physical activity and mental health – be it preventing the onset depressive or anxious symptoms to minimizing the prognosis of certain conditions – we posit more emphasis be placed in health communications on physical activity as a coping strategy for Canadians. As the ramifications of COVID-19 continue, coupled with the concern of a pending second wave, identifying how Canadians are managing stress and mental health can inform the development of interventions aimed at mitigating the negative impact of COVID-19 on adults’ overall wellness. Herein we explore how a representative sample of Canadian adults are coping with increased stress and mental health issues as a result of COVID-19 and identify a potential disconnect between considering physical activity as a strategy to support social connection and stress management and how Canadians are coping with the pandemic. Given the protective role of physical activity in supporting mental health, our perspective is that health communication efforts should focus on the mental health benefits of physical activity particularly during these uncertain times.